2011
DOI: 10.15388/omee.2011.2.1.14291
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and Consequences of Status Consumption Among Urban Vietnamese Consumers

Abstract: This study examines the antecedents and consequences of status consumption in the transitional economy of Vietnam. Both qualitative (focus groups and in-depth interviews) and quantitative methods (survey) were employed in this investigation. To test the proposed model and hypotheses, a large consumer survey was conducted in the two biggest cities in Vietnam. The results of Structural Equation Modeling provided empirical evidence for the significant impact of most of the proposed antecedents of status consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…Third, this study verifies the positive and significant relationship between consumer ethnocentrism in developing countries, with conspicuous consumption, based on previous studies by Karoui and Khemakhem ( 2019 ), Kavak and Gumusluoglu ( 2007 ), and Mai and Tambyah ( 2011 ); in this way, it can be observed that people in emerging markets, although they may be ethnocentric, when the purchase of foreign products generates social status, and, in addition, these products are part of the symbols of national identity, negative feelings toward them are not generated.…”
Section: Discussion Research Implications and Limitationssupporting
confidence: 79%
“…Third, this study verifies the positive and significant relationship between consumer ethnocentrism in developing countries, with conspicuous consumption, based on previous studies by Karoui and Khemakhem ( 2019 ), Kavak and Gumusluoglu ( 2007 ), and Mai and Tambyah ( 2011 ); in this way, it can be observed that people in emerging markets, although they may be ethnocentric, when the purchase of foreign products generates social status, and, in addition, these products are part of the symbols of national identity, negative feelings toward them are not generated.…”
Section: Discussion Research Implications and Limitationssupporting
confidence: 79%
“…According to Eastman and Liu (2012), status consumption is motivational processes in which individuals try to improve financial status through the use or consumption of products that become symbolic of status for individuals and their environment. Mai and Tambyah (2011) write status consumption as the consumption of goods and services that can display the status of the users or consumers. As a strong motivation for shopping, the status consumption has one measurement, an interest in consuming for status, which is derived into two indicators of conspicuous consumption and a desire for status (Eastman & Liu, 2012).…”
Section: Status Consumptionmentioning
confidence: 99%
“…Status consumption is considered as a kind of individual trait (Chui & Sidin, 2011) and is an individual difference at different levels, in different consumers and associated with income, social classes, education and living area. Because status consumers want to be recognized and differentiated in the group, they think that certain products convey status and prestigious (Clark, Zboja & Goldsmith, 2007;Mai & Tambyah, 2011). Eastman and Eastman (2011:10) expressed this situation well, "status seekers are people who are continually straining to surround themselves with visible evidence of the superior rank they are claiming".…”
Section: Status Consumptionmentioning
confidence: 99%